Formulasi dan Evaluasi Sifat Fisik Sediaan Shampo dari Ekstrak Daun Sungkai (Peronema Canescens Jack) - Mariska, Ruri Putri; As'adi, M. Henityo Agung; Ibriyanti, Silda (Universitas Baiturrahim, 2025)
Shampoo is one of the scalp care preparations used to clean dirt on the scalp and dandruff. Shampoo preparations with active ingredients made from natural ingredients have good effectiveness and safer safety compared to the use of shampoos whose active ingredients are taken from synthetic materials. One of the active ingredients comes from nature that can be used as a shampoo preparation, namely the sungkai plant (Peronema canescens Jack). Sungkai leaves have secondary metabolites, namely alkaloids, flavonoids, terpenoid-steroids, and tannins. Flavonoids are secondary metabolites that function as antioxidants and antibacterials. The purpose of this study was to determine which one can produce the best formula for shampoo preparations from sungkai leaf extract (Peronema canescens Jack) and to determine the characteristics of the physical properties of sungkai leaf shampoo preparations (Peronema canescens Jack). Shampoo preparations were tested for organoleptic, pH, stability, foam height, viscosity and preference. The evaluation results obtained were analyzed descriptively. The results of this study in each evaluation test of shampoo preparations have met the requirements and good formulas, namely in formula 1.